"The world is losing this little girl": An exploration of hospital-based Children's End of Life Care through a Narrative Lens - Jones, Anne Marie (Trinity College Dublin. School of Social Work & Social Policy. Discipline of Social Studies, 2021)
The death of a child is a profound and life-changing loss for all families. The majority of children continue to die in hospital due to the nature of the child's illness, the suddenness of their deterioration, and, at times, parental choice. The lack of research in this field in Ireland was one of the motivations for this study. Based in an acute children's hospital during a period of transition and amalgamation into a larger entity, the rationale for this study was to explore the experiences of families whose child was provided End of Life Care (EOLC) in the hospital and subsequently died, and the staff who cared for them. Using a Narrative approach, the study is framed within a social constructionist perspective on bereavement, highlighting the belief that death occurs within a social context. 15 parents who had experienced the death of a child 6 months to two and a half years prior to being interviewed, were invited to share their experience through the use of a two part in-depth interview which took place in their own home or at the research site according to their wishes. In addition, 24 staff members at the research site were interviewed in focus groups using the same approach. Reflective Thematic Analysis was used as the method of analysis across all interviews, and narrative analysis was used to identify unique and enabling experiences from the interviews. From the analysis of the parent interviews, three major themes emerged which reflected Turner's (1967) concept of "liminality" representing the changes that occur as families go through this key rite of passage. These themes convey parents' experiences of separating from their known world and entering into the complex and challenging world of EOLC. The focus groups for health care professions emphasised the complexities of the work in this area as well as the personal impact on staff. Further findings from a narrative reading of the data brought relationships between parents and staff to the fore. The role of staff in enabling moments of lasting significance for parents with their children is revealed. The findings from the study have been integrated into a "Map of Narrative Practice in Children's End of Life Care", highlighting the importance of relationship-based care, based on a shared sense of humanity around the tragic death of a child. This research emphasises the importance of communication and actions recognising the unique relationship between parents and their child and their deep emotional connection. By adopting a social constructionist and narrative approach, hospital-based children's EOLC can provide spontaneous opportunities to promote positive adjustment and endeavouring to minimise future complications in what is one of the most difficult bereavements.
APPROVED
Keywords: Narrative; End-Of-Life Care; Hospital; Child; Social Work